(untitled) (Brazilian Journal of Health Research, 2025)
Introduction: Congenital anomalies of the lower intestinal tract are important causes of morbidity in neonates, initially presenting with clinical and radiographic findings that suggest intestinal obstruction. Congenital short colon syndrome, colonic atresia and Hirschsprung’s disease have been reported more frequently, while colon agenesis is rarer and, in the few reported cases, is associated with other abdominal malformations. Case report: A male patient with normal prenatal exams and a normal delivery presented hypoglycemia in the first hours of life, progressing to abdominal distension and nausea after the first feeding. He underwent gastric lavage with meconium and anal probing, which demonstrated suspected intestinal obstruction. A simple abdominal radiograph was performed, which showed intestinal obstruction. He underwent laparotomy, where the rectum and colon were found to be absent. A 10 cm resection of the distal portion of the ileum was performed, with the creation of an ileostomy. The patient was discharged. Approximately 10 months later, he was hospitalized again with suspected intestinal obstruction, confirmed by abdominal computed tomography, and underwent resection of the entire small intestine, maintaining parenteral nutrition in the postoperative period. Conclusion: The imaging findings in colonic agenesis are not very specific, reflecting the findings of low intestinal obstruction. From a radiological point of view, simple and contrast radiography are important allies in the diagnosis of colonic agenesis, due to their easy access and low cost. Since the treatment is surgical, knowledge of the images and their correct description help in the rapid follow-up of the case.